Change of dietary patterns on CO2 emissions under the African swine fever in South Korea - Eun, Sungtae (Frontiers in Climate, 2024)
African swine fever (ASF) occurred in Gyeonggi of South Korea in 2019 and there were 21 reported cases in domestic swine farms. South Korea is the one of top countries for pork consumption, and half of the 2.9 million tons of meat consumed in 2022 were pork. Outbreaks from animal products have a severe impact on the shift of diet and the change in dietary patterns of consumers shape climate change. Moreover, animal products account for 18% of worldwide GHG emissions which is more than industry (16%), transportation (13.5%), and energy usage (13%). This study is the first study to analyze the regional impact of animal products associated with climate change in South Korea. The objective of this study is to analyze the regional effect of dietary shifts on per capita CO2 emissions from household consumption in South Korea. Synthetic Control Method (SCM) is employed to analyze the impact of ASF on the change of per capita CO2 emissions from household consumption by shifting the nutritional patterns in South Korea. The dependent variable is per capita CO2 emissions from household consumption, and the type of event is an epizootic disease. The event period is between 2010 and 2021 (pre-intervention: 2010–2018 and post-intervention: 2019–2021). By establishing synthetic Gyeonggi from the optimal synthetic control unit, the trajectories present how dietary shifts have influenced per capita CO2 emissions from household consumption in a positive direction after ASF. ASF caused consumer dietary shifts from pork to other types of meat. This divergence between Gyeonggi and synthetic Gyeonggi indicates that there is an impact influencing per capita CO2 emissions from household consumption after ASF. Performing an SCM analysis with the treated (Gyeonggi) and control (thirteen municipalities) units, the study found that the two trajectory lines (Gyeonggi and synthetic Gyeonggi) were similar before diverging after the introduction of ASF. The gaps also indicate the impact of the shift in dietary patterns on per capita CO2 emissions from household consumption.JEL classificationC31, Q54.